2013
DOI: 10.1144/sp381.10
|View full text |Cite
|
Sign up to set email alerts
|

A review of geomorphic processes and landforms in the Dry Valleys of southern Victoria Land: implications for evaluating climate change and ice-sheet stability

Abstract: The Dry Valleys are subdivided into three microclimate zones on the basis of summertime measurements of atmospheric temperature, soil moisture, relative humidity and wind-speed/ direction. Subtle variations in these climate parameters result in considerable differences in process geomorphology and in the development of unique landforms within each zone. The mapped zones include a coastal thaw zone, an inland mixed zone and a stable upland zone. Landforms within each zone are subdivided into macroscale features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 210 publications
(307 reference statements)
0
34
0
Order By: Relevance
“…Clasts at the ground surface tend to stay at the surface; they are not subjected to repeated episodes of burial and reexposure as is typical of saturated active layers in the Arctic [ Hallet and Waddington , ] or even within the relatively warm soils in low‐elevation coastal regions adjacent to McMurdo Sound [ Marchant and Head , ]. The implication is that small‐scale weathering features on exposed rock surfaces are most probably related to atmospheric processes, rather than to impacts, collisions, or physical/chemical weathering associated with clast movement and burial/reexposure via cryoturbation [ Marchant et al ., ].…”
Section: Background and Physical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Clasts at the ground surface tend to stay at the surface; they are not subjected to repeated episodes of burial and reexposure as is typical of saturated active layers in the Arctic [ Hallet and Waddington , ] or even within the relatively warm soils in low‐elevation coastal regions adjacent to McMurdo Sound [ Marchant and Head , ]. The implication is that small‐scale weathering features on exposed rock surfaces are most probably related to atmospheric processes, rather than to impacts, collisions, or physical/chemical weathering associated with clast movement and burial/reexposure via cryoturbation [ Marchant et al ., ].…”
Section: Background and Physical Settingmentioning
confidence: 99%
“…The spalling or detachment of thin flakes from exposed rock surfaces is an important erosional process operating across a range of rock types and climatic settings. Understanding the precise mechanisms responsible for spalling helps elucidate rates of long‐term erosion and landscape evolution [ Marchant et al ., ]; assists in the development of process models used to interpret the inventory of cosmogenic nuclides in surface rocks [ Gordon and Dorn , ; Gunnell et al ., ; Mackay and Marchant , ; Muzikar , , ]; and documents the potential for degradation of building stones, rock art, and monuments [ Benito et al ., ; Cardell et al ., ; Hall et al ., ; McCabe et al ., ; Mol and Viles , ].…”
Section: Introductionmentioning
confidence: 99%
“…Stagnant blocks of glacial ice are common at the margins of retreating glaciers on Earth, and may have existed and been preserved on Mars by a thick insulating layer of sublimation till. Thermal cycling and erosion of the exposed plateau scarps contributed to rockfalls and rockslides on top of the glacial ice, as seen in the McMurdo Dry Valleys (Swanger et al, 2010;Kowalewski et al, 2011;Marchant et al, 2013;MacKay et al, 2014). Through this process, a rocky supraglacial till developed and was integrated with the dust-rich sublimation lag produced from initial downwasting of the ice-sheet.…”
Section: Ice-sheet Retreatmentioning
confidence: 99%
“…In an effort to elucidate the climatic significance of some long‐lived viscous flow features in Antarctica, we initiated in 1995 a suite of detailed geomorphological and geophysical studies of buried ice in interior regions of the McMurdo Dry Valleys (MDV) [ Kowalewski et al ., , , ; Marchant and Head , ; Marchant et al ., ; Sugden et al ., ; Swanger and Marchant , ; Swanger et al ., ]. Our initial results demonstrated that buried ice can survive for millions of years [ Marchant et al ., ; Sugden et al ., ], that sublimation and subsequent vapor diffusion through capping debris can be extremely slow on the order of <10 −1 mm a −1 [ Kowalewski et al ., , , ; Marchant et al ., ], and that the origin of buried ice deposits varies with local microclimate conditions [ Marchant and Head , ; Marchant et al ., ; Swanger et al ., ]. Here we focus on the origin and internal ice‐flow dynamics of two viscous flow features, previously mapped as cold‐based debris‐covered alpine glaciers: the Mullins valley and Friedman valley debris‐covered glaciers (hereafter informally termed Mullins Glacier and Friedman Glacier).…”
Section: Introductionmentioning
confidence: 98%